Batteries: SiO2/TiO2 Composite Film for High Capacity and Excellent Cycling Stability in Lithium‐Ion Battery Anodes (Adv. Funct. Mater. 39/2017). (17th October 2017) - Lee, Gibaek; Kim, Sudeok; Kim, Sunkyu; Choi, Jinsub
Abstract : The universe is known as a matter consisting of 99.999% plasma. In article number1703538, Jinsub Choi and co‐workers prepare plasma in the electrolyte under high voltage conditions, so‐called plasma electrolyte oxidation (PEO). This allows the formation of SiO2 ‐TiO2 nanocomposites on a Ti substrate, in which SiO2 and TiO2 are designed to contribute to high capacity and excellent cycling stability of Li‐ion batteries, respectively.